Development and validation of a risk nomogram predicting pneumothorax requiring chest tube placement post-percutaneous CT-guided lung biopsy - Masha Bondarenko; Jianxiang Zhang; Ulysis Hugo Baal; Brian Lam; Gunvant Chaudhari; Yoo Jin Lee; Jamie Schroeder; Maya Vella; Brian Haas; Thienkhai Vu; Kimberly Kallianos; Jonathan Liu; et al. (BMC Medical Imaging)
Abstract Background Pneumothorax requiring chest tube after CT-guided transthoracic lung biopsy presents added clinical risk and costs to the healthcare system. Identifying high-risk patients can prompt alternative biopsy modes and/or better preparation for more focused post-procedural care. We aimed to develop and externally validate a risk nomogram for pneumothorax requiring chest tube placement following CT-guided lung biopsy, leveraging quantitative emphysema algorithm. Methods This two-center retrospective study included patients who underwent CT-guided lung biopsy from between 1994 and 2023. Data from one hospital was set aside for validation (n = 613). Emphysema severity was quantified and categorized to 3-point scale using a previously published algorithm based on 3×3×3 kernels and Hounsfield thresholding, and a risk calculator was developed using forward variable selection and logistic regression. The model was validated using bootstrapping and Harrell’s C-index. Results 2,512 patients (mean age, 64.47 years ± 13.38 [standard deviation]; 1250 men) were evaluated, of whom 157 (6.7%) experienced pneumothorax complications requiring chest tube placement. After forward variable selection to reduce the covariates to maximize clinical usability, the risk score was developed using age over 60 (OR 1.80 [1.15–2.93]), non-prone patient position (OR 2.48 [1.63–3.75]), and severe emphysema (OR 1.99 [1.35–2.94]). The nomogram showed a mean absolute error of 0.5% in calibration and Harrell’s C-index of 0.664 in discrimination in the internal cohort. Conclusion The developed nomogram predicts age over 60, non-prone position during biopsy, and severe emphysema to be most predictive of pneumothorax requiring chest tube placement following CT-guided lung biopsy.